Rare Tumors Causing Median Nerve Compression in Adults—A Narrative Review - Natroshvili, Tinatin; Peperkamp, Kirsten; Malyar, Masoud A.; Wijnberg, David; Heine, Erwin P.; Walbeehm, Erik T. (Archives of Plastic Surgery, 2022)
The median nerve can be compressed due to a tumor along the course of the median nerve, causing typical compression symptoms or even persistence or recurrence after an operation. The aim of this review is to provide a comprehensive overview of rare tumors described in recent publications that cause median nerve compression and to evaluate treatment options.The PubMed, Embase, and Web of Science databases were searched for studies describing median nerve compression due to a tumor in adults, published from the year 2000 and written in English. From 94 studies, information of approximately 100 patients have been obtained.Results The rare tumors causing compression were in 32 patients located at the carpal tunnel, in 21 cases in the palm of the hand, and 28 proximal from the carpal tunnel. In the other cases the compression site extended over a longer trajectory. There were 37 different histological types of lesions. Complete resection of the tumor was possible in 58 cases. A total of 8 patients presented for the second time after receiving initial therapy. During follow-up, three cases of recurrence were reported with a mean follow-up period of 11 months.The most common published cause of median nerve compression is the lipofibromatous hamartoma. Besides the typical sensory and motor symptoms of median nerve compression, a thorough physical examination of the complete upper extremity is necessary to find any swelling or triggering that might raise suspicion of the presence of a tumor.
Keywords: median neuropathy; neoplasms; rare diseases